Case study of power generation and CO2 emissions reduction potential from introduction of Organic Rankine Cycle on Atyrau Oil Refinery Plant Vacuum Distillation Unit. (2018) - Tokmurzin, Diyar; Otarov, Rustam; Aiymbetov, Berik; Bulatov, Igor; Smith, Robin
Abstract: Typically process industries use high-temperature thermal energy in their multiple processes and reject low-temperature heat through cooling water and cooling towers. An introduction of low-grade heat utilization processes such as Organic Rankine Cycle (ORC) for electricity production can be considered as a viable technology for saving energy and reducing CO2 emissions. ORC market penetration is rather limited due to a difficulty of prospective investors and end-users to realize the energy saving potential. This case study investigates opportunities for introduction of ORC system on a Vacuum Distillation Unit (VDU) of Atyrau Oil Refinery plant (AORP). ORC system integration is analyzed using Pinch analysis heat integration method. Suitable temperature range, process streams were identified and ORC system simulation conducted using ASPEN HYSYS